Tragedi World Trade Center (9/11) dan dampaknya terhadap Islamofobia di Prancis: Tinjauan fenomenologi Edmund Husserl - Fahira, Hafizhah Almas (Maliki Interdisciplinary Journal, 2024)
The phenomenon of the 2001 World Trade Center tragedy or 9/11 in 2001 had a major influence on the stability of Muslims throughout the world. Islamophobia affecting Muslims, especially in the West, especially France, is increasing. They often receive all forms of discrimination and exclusion as a result of the bad stigma that Islam receives. The subjective views of individual people in interpreting this phenomenon make them behave discriminatorily towards Muslims. This research aims to explain the relationship between the 9/11 tragedy and the increase in Islamophobia in France, describe several forms of Islamophobic behavior in France, and explain the true nature of Islamic teachings and values. Meanwhile, in this research, researchers used qualitative descriptive analysis research methods to analyze the World Trade Center terrorism tragedy and its impact on increasing the issue of Islamophobia in France. The theory used in this research is Edmund Husserl's phenomenology. The results of this research show that many ordinary people in the West, especially France, are consumed by Western media and therefore behave in a discriminatory manner and practice Islamophobia. The 9/11 incident also showed that it was the main factor increasing Islamophobia in the West, especially France. This research also shows that the true religion of Islam is a religion that loves peace because it is in line with the commands of Allah SWT in the words of the Koran such as Q.S. Al-Hujurat verse 13.